Effects of prednisolone on energy and fat metabolism in patients with rheumatoid arthritis: tissue‐specific insulin resistance with commonly used prednisolone doses. (21st July 2016) - Radhakutty, Anjana; Mangelsdorf, Brenda L.; Drake, Sophie M.; Samocha‐Bonet, Dorit; Heilbronn, Leonie K.; Smith, Malcolm D.; Thompson, Campbell H.; Burt, Morton G.
Summary: Objective: Glucocorticoids can cause postprandial hyperglycaemia, but the effects on postprandial energy and fat metabolism are uncertain. We investigated the effects of acute and chronic low‐dose prednisolone on fasting and postprandial energy expenditure and substrate metabolism. Design: An open interventional and cross‐sectional study was undertaken. Patients and measurements: Eighteen patients who had not taken oral glucocorticoids for ≥6 months were studied before and after 7 days prednisolone (6 mg/day) to assess the acute effects of prednisolone. Baseline data from patients, not on glucocorticoids, were compared with 18 patients on long‐term prednisolone (6·5 ± 1·8 mg/day for >6 months) to assess the chronic effects. Energy expenditure and substrate oxidation were measured using indirect calorimetry before and after a mixed meal. Adipocyte insulin resistance index and insulin‐mediated suppression of NEFA were calculated from fasting and postprandial insulin and NEFA concentrations. Results: There were no significant differences in resting energy expenditure or diet‐induced thermogenesis with prednisolone. Acute (−2·1 ± 6·2 vs −16·3 ± 4·8 mg/min, P = 0·01) and chronic (−1·4 ± 2·8 vs −16·3 ± 4·8 mg/min, P = 0·01) prednisolone attenuated postprandial suppression of fat oxidation. Chronic (31·6 ± 3·8 vs 17·0 ± 3·3, P = 0·007), but not acute, prednisolone increased adipocyte insulin resistance index. However, insulin‐mediated suppression of NEFA was not significantly different after acute or chronic prednisolone. Conclusions: Prednisolone does not alter energy expenditure. However, even at low doses, prednisolone exerts adverse effects on fat metabolism, which could exacerbate insulin resistance and increase cardiovascular risk. Attenuated postprandial suppression of fat oxidation, but not lipolysis, suggests that prednisolone causes greater insulin resistance in skeletal muscle than in adipocytes.